2017
DOI: 10.18632/oncotarget.22521
|View full text |Cite
|
Sign up to set email alerts
|

The survival benefit of neoadjuvant chemotherapy and pCR among patients with advanced stage triple negative breast cancer

Abstract: Triple negative breast cancer (TNBC) is an aggressive subtype that accounts for 15-20% of cases, with a higher incidence of relapse/death. Even with adjuvant chemotherapy, the 5 year distant metastasis-free survival rate remains low. A total of 452 tumor registry patients with TNBC and no evidence of metastatic disease were identified over the period of 1996-2011. The median age and follow-up time were 51 (range=21-88) and 3.9 (range=0.14-14) years. Approximately 75% of patients with stage III disease received… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
48
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(68 citation statements)
references
References 29 publications
2
48
0
Order By: Relevance
“…As regards external validity, convergent validity was acceptable and a pattern of significant correlations with health outcomes was observed in the expected direction. This is particularly relevant, since adjuvant chemotherapy is the treatment of choice after surgery for certain locally advanced cancers, such as breast and colon cancer, and treatment tends to have immediate, negative repercussions for patients' physical status, symptomatology, and global QoL 29 , although their adverse effects are usually temporary 29 . Our results indicate that the patients most likely to regret treatment are those with worse QoL, including physical status, presence of symptoms, and greater psychological distress.…”
Section: Discussionmentioning
confidence: 99%
“…As regards external validity, convergent validity was acceptable and a pattern of significant correlations with health outcomes was observed in the expected direction. This is particularly relevant, since adjuvant chemotherapy is the treatment of choice after surgery for certain locally advanced cancers, such as breast and colon cancer, and treatment tends to have immediate, negative repercussions for patients' physical status, symptomatology, and global QoL 29 , although their adverse effects are usually temporary 29 . Our results indicate that the patients most likely to regret treatment are those with worse QoL, including physical status, presence of symptoms, and greater psychological distress.…”
Section: Discussionmentioning
confidence: 99%
“…Complications and side effects are also major issues . Large multi‐center studies conducted in Australia, Asia, Europe, and the United States (US) have shown that NACT could achieve pathological complete response in HR−/HER2+ and triple negative tumors, which serves as a strong prognostic factor for longer overall survival …”
Section: Introductionmentioning
confidence: 99%
“…27 Large multi-center studies conducted in Australia, Asia, Europe, and the United States (US) have shown that NACT could achieve pathological complete response in HR−/HER2+ and triple negative tumors, which serves as a strong prognostic factor for longer overall survival. 21,[28][29][30] This study was conducted to describe the utility of surgical modalities in different age and histologic groups and to determine the changing trends between 2006 and 2015.…”
Section: Introductionmentioning
confidence: 99%
“…The elegant progress of target therapies in HR+/ Her-2+ BC forced the investigators to recognize target therapies in TNBC. The introduction of AR evaluation in these subgroups of patients is really a huge step forward as it may help to determine the disease behavior (Biswas et al, 2017).…”
Section: Discussionmentioning
confidence: 99%